2014
DOI: 10.1177/0734242x14532004
|View full text |Cite
|
Sign up to set email alerts
|

Thermal treatment of solid waste in view of recycling: Chromate and molybdate formation and leaching behaviour

Abstract: Elevated Cr and Mo concentrations are often found in leachates of thermally treated solid waste, but there is no general explanation for this so far. Therefore, we studied the leaching behaviour after thermal treatment as a function of heating temperature and residence time for two types of solid waste: contaminated sludge and bottom ash from municipal solid waste incineration. The leaching behaviour of both waste streams was compared with experiments on synthetic samples, allowing deduction of a general mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…FeO x was more concentrated in the bigger size fractions of BA (fraction M) due to its mechanical resistance and contained the majority of Zn, Cu and Ni (Table 4), which led to the higher contents of these PTEs released from M. Interestingly, in the F1 extraction solutions (initial pH 2.85) from both fractions, no antimony was detected. Although, anti-mony from MSWI bottom ash is reported to be leachable at acidic pH (Verbinnen et al, 2014). Furthermore, the leaching analysis according to column leaching test showed the presence of leach-Fig.…”
Section: Mineralmentioning
confidence: 95%
“…FeO x was more concentrated in the bigger size fractions of BA (fraction M) due to its mechanical resistance and contained the majority of Zn, Cu and Ni (Table 4), which led to the higher contents of these PTEs released from M. Interestingly, in the F1 extraction solutions (initial pH 2.85) from both fractions, no antimony was detected. Although, anti-mony from MSWI bottom ash is reported to be leachable at acidic pH (Verbinnen et al, 2014). Furthermore, the leaching analysis according to column leaching test showed the presence of leach-Fig.…”
Section: Mineralmentioning
confidence: 95%
“…It is therefore difficult to link the lab experiments to the sudden mineralogy change predicted by the thermochemical calculations. Verbinnen et al [67] reported a similar decrease when leaching Cr with water from contaminated sludge incinerated at temperatures ranging between 400 and 900 °C. They suggested that the highly soluble chromates present at low temperatures will start to form a silicate melt as the incineration temperature increases, in this way preventing the Cr from leaching [67].…”
Section: Heavy Metal Extractionmentioning
confidence: 81%
“…After 30 min, the produced aggregates were removed from the furnace and allowed to cool at room temperature. The temperature and residence time were chosen based on the results from earlier research (Verbinnen et al, 2013a(Verbinnen et al, , 2014, in which was shown that 30 min at 1100 °C was optimal for stabilizing oxyanion forming compounds like Cr and Mo (Figure 1), and for obtaining lightweight aggregates. Other toxic elements as given in Table 1, are stabilized at lower temperatures (Table 1).…”
Section: Ceramics Productionmentioning
confidence: 99%
“…This indicates that Mo is effectively stabilized in the matrix of the sludge during heat treatment. Indeed, Mo is incorporated in a glassy phase at temperatures of 1100°C (Verbinnen et al, 2014), preventing it from leaching. The elevated temperature is needed to form aggregates with high mechanical strength and to effectively stabilize Mo and Cr, but is far lower than the temperatures that are reported for similar waste streams that are stabilized by full vitrification of the materials (typically 1400 -1500 °C, Li et al, 2007;Bingham and Hand, 2006;Kavouras et al, 2003).…”
Section: Leaching Of Mo From Ceramic Materialsmentioning
confidence: 99%
See 1 more Smart Citation